2012
DOI: 10.1111/j.1600-0447.2011.01823.x
|View full text |Cite
|
Sign up to set email alerts
|

Moderators of the synchrony of change between decreasing depression severity and disability

Abstract: Moderators of the synchrony of change between decreasing depression severity and disability Verboom, C. E.; Ormel, J.; Nolen, W. A.; Penninx, B. W. J. H.; Sijtsema, J. J. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
4
1
Order By: Relevance
“…[27] Still, even if no deterioration is apparent, it would be interesting to observe factors associated with a slower recovery in functioning. For example, although not found in the present sample with subthreshold symptoms, Verboom et al [45] found that among persons recovering from full-syndromal MDD, higher age was associated with a slower recovery in functioning over time.…”
Section: Discussioncontrasting
confidence: 77%
“…[27] Still, even if no deterioration is apparent, it would be interesting to observe factors associated with a slower recovery in functioning. For example, although not found in the present sample with subthreshold symptoms, Verboom et al [45] found that among persons recovering from full-syndromal MDD, higher age was associated with a slower recovery in functioning over time.…”
Section: Discussioncontrasting
confidence: 77%
“…Our results demonstrate strong correlations between (last week) experienced symptom distress and (last month) experienced disability. These results are consistent with research by Verboom et al (2012) andKa (2009) and with the conceptualization of mental disorders in DSM-5 (American Psychiatric Association, 2013). Indeed, the DSM-5 definition of a mental disorder consists of both concepts: clinically significant distress (e.g., painful symptoms) and/or disability (i.e., impairment in one or more important areas of functioning; American Psychiatric Association, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…The current study has three aims: first, we will investigate the relationship between symptom distress and experienced disability at three measurement points in a two-year period. Based on earlier research (McKnight et al, 2016;Verboom et al, 2012) we expect moderate to strong correlations for this relation. Second, we are interested in the differences in the effects of the symptom reduction and reduction in experienced disability in patients that receive evidence-based psychotherapy for mood and anxiety disorders in routine clinical practice.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Although this may be a proxy for depression severity, we added functional impairment, because of its association with factors that influence course and treatment response that are indirectly related to depression, especially in chronic MDD (Frank et al, 2011). Patients with identical levels of depression severity may function differently in their daily lives because of differences in social support or economic resources (Verboom et al, 2012(Verboom et al, , 2011. For simplicity and acceptability, we operationalized functional impairment based on the GAF-scale of the DSM-IV (APA, 1994(APA, , 2000, which is routinely assessed in clinical practice.…”
Section: Functional Impairmentmentioning
confidence: 99%